Developmental toxicity and risk assessment of nonylphenol to the South American toad, Rhinella arenarum - Aronzon, Carolina Mariel (2014)
The toxicity of Nonylphenol, an emerging pollutant, on the common South American toad Rhinella arenarum was stage and time dependent, thus Median Lethal Concentrations (LC50) for acute (96 h), short-term chronic (168 h) and chronic exposure (336 h) were 1.06; 0.96 and 0.17 mgNP/L from embryonic period (S.4), whereas for exposure from larvae (S.25), LC50 remained constant at 0.37 mgNP/L from 96 h to 168 h, decreasing to 0.11 mgNP/L at 336 h. NOEC-168 h for exposure from embryos was 0.025 mgNP/L. The Teratogenic Potential (NOEC-lethality/NOEC-sublethal effects) was 23 times higher than the threshold value, indicating a high risk for embryos to be malformed in absence of significant lethality and representing a threat for the species conservation. By comparing with other amphibians, the early development of R. arenarum was very sensitive to NP. The results highlight the relevance of extending the exposure time and look for the most sensitive stage in order to perform the bioassays for conservation purposes.